Pengelolaan Bisnis Sanggar Senam Aerobik di Kabupaten Rembang (Universitas Negeri Semarang, 2021)
The background of this research is from the many sports, there is one sport that is popular and much in demand by all circles today, namely aerobic gymnastics. So there are some of the people in Rembang Regency established a gymnastics workshop business because it can make a promising and profitable business for the owner. However, more than one gymnastics workshop in Rembang Regency that does not know how to manage the workshop to become a growing business, this research uses qualitative descriptive methods by collecting data using observation techniques, interviews and documentation. Qualitative data analysis uses 3 stages, namely data reduction, data presentation and conclusion drawing. The targets in this study are owners or managers, instructors and members. The results of the research include the following aspects of business management, namely covering human resources are already running well but still need to be increased the number of managers for the smooth management of the workshop. The infrastructure of the three gymnastics workshops that have been studied is only one gymnastics workshop that can almost be said both according to the needs and use of facilities. The finances of the three gymnastics workshops are only one workshop that manages the finances and the bookkeeping has been detailed. The operations that have been carried out by these three workshops have been good by minimizing according to the needs of the member schedule. The marketing of the three gymnastics workshops is different two of the three workshops conduct gymnastics demonstration activities with a very creative, while 1 of the other 2 gymnastics workshops do not really understand how to promote a managed gymnastics gym. Conclusions from the three workshops to better understand how to manage the workshop well and can look at the categories of aspects that are already available. Advice for workshops that have not implemented aspects in the management of the workshop in order to further relearn the aspects needed to manage a gymnastics workshop.